A universal deposition protocol for planar heterojunction solar cells with high efficiency based on hybrid lead halide perovskite families - Conings, B; Babayigit, A; Klug, M; Bai, S; Gauquelin, N; Sakai, N; Wang, J; Verbeeck, J; Boyen, H; Snaith, H (Wiley, 2016)
A robust and expedient gas quenching method is developed for the solution deposition of hybrid perovskite thin films. The method offers a reliable standard practice for the fabrication of a non-exhaustive variety of perovskites exhibiting excellent film morphology and commensurate high performance in both regular and inverted structured solar cell architectures.